Blood-Biochemical Profile During Retention Of Placenta (Rop) In Crossbred Cattle - Sheetal, S. K.; Choudhary, S. K.; Sengupta, D.; Kumari, Punita; Bharti, S. K. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present investigation was carried out to study the blood-biochemical profile during retention of placenta in crossbred cattle. Serum glucose and cholesterol level were significantly higher whereas there was non significant higher protein level was observed in non ROP ,as compared to ROP cows
Keywords: Blood-biochemical profile; Retention of placenta; Parturition